Pengembangan Bahan Ajar Efektif Untuk Anak Usia Pra Sekolah: Perspektif Model High Scope - Murni, Rita Kartika; Halqi, Muhammad; Murcahyanto, Hary (Journal of Elementary School (JOES), 2024)
This study aims to develop teaching materials based on the High Scope learning model to increase the learning motivation of children aged 3-4 years at TPA Segara Anak Selong. The High Scope model was chosen because it emphasises the active involvement of children in learning, with the teacher as a facilitator. The research adopted the Borg and Gall research and development method with six steps, involving observation, planning, initial product development, initial field trials, revision, and field trials. These stages included the design of teaching materials, development of evaluation instruments, and validation by material experts and linguists. The validation results showed that the teaching materials were categorised as "very good" from material experts and "good" from linguists. The initial field trial involved 15 children aged 3-4 years at TPA Segara Anak Selong. Observation data was converted into scores and analysed to assess the increase in children's learning motivation. The results showed a significant increase in learning motivation. Revisions were made based on feedback from the initial field trial. This research contributes to the development of High Scope-based teaching materials to increase early childhood learning motivation. Keywords: Early Childhood, High Scope, Teaching Materials Development